Perlindungan Konsumen Garansi Layanan Purna Jual Pada Marketplace - Zaprullah, Heri; Fuad, Fokky (UNES Law Review, 2024)
After-sales service is closely related to the product warranty period. If the warranty period expires earlier than promised, consumers may lose their right to claim damages, Therefore, the research will focus on how the implementation of after-sales services affects the protection of consumer rights and the responsibility of businesses. According to Article 1 paragraph (2) of Law Number 8 of 1999 concerning Consumer Protection. The formulation of the problem in this study is how is the legal protection for consumers in the after-sales service warranty. This research uses the Normative Empirical Research Method which is carried out by collecting data using the Questionnaire Technique. Collecting data through questionnaires is expected to help analyze the importance of the role of warranty service selling products. This way can assess the consistency or difference in the information obtained from the source of the questionnaire. The results showed that from the questionnaire data obtained 82.6% of respondents answered that they had received a warranty guarantee from the store they bought. This is in accordance with the provisions of Article 7 of the Consumer Protection Law.